Separation of CH4/N2 of Low Concentrations From Coal Bed Gas by Sodium-Modified Clinoptilolite - Hao, Xiaofei; Li, Zhen; Hu, Hongjie; Liu, Xueqin; Huang, Yanqiu (Frontiers in Chemistry, 2018)
Clinoptilolite is a widely distributed tectosilicate, mainly composed of Al2O3, SiO2 with exchangeable cations such as Ca, K, Mg, and Na. In this research, raw clinoptilolite was ground, gravimetrically concentrated and ion-exchanged using different concentrations of NaCl solution. Then the modified clinoptilolite powder was formulated into particles as adsorbents. The adsorbents were applied to CH4 separation in coal bed gas. The raw and modified clinoptilolites were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), atomic emission spectrometer (ICP-AES), Fourier transform infrared spectrometer (FTIR), and Brunauer Emmett Teller (BET) specific surface area. The CH4 absorptivity by raw and modified clinoptilolites was evaluated using pressure swing adsorption (PSA) to assess the CH4 separation ability. The results indicated that the ion-exchanged clinoptilolite using 0.2 mol/L NaCl solution was found to be promising for the kinetic PSA separation of CH4/N2, giving a better absorptivity for CH4 separation under different influence factors. Based on the simulated static experiments, it was indicated that both CH4 and N2 were capable of diffusing into clinoptilolite while N2 adsorption by clinoptilolite was excellent. The experiment results also indicated that ion-exchanged clinoptilolite using a 0.2 mol/L NaCl solution was the optimal adsorbent for separating CH4/N2 at the low pressure condition. From the simulated dynamic experiments, the ion-exchanged clinoptilolite using a 0.2 mol/L NaCl solution as a potential sorbent in kinetic PSA processes for N2/CH4 separation, exhibited the best performance at 648 K under 0.2 MPa within 28 min, in comparison to the raw clinoptilolite and clinoptilolite under other modification conditions. In the next phase of research, the modified clinoptilolite will be tested for CH4 separation in real coal bed gas.